Genetic analysis of dTSPO, an outer mitochondrial membrane protein, reveals its functions in apoptosis, longevity, and Aβ42‐induced neurodegeneration. Issue 3 (21st February 2014) - Lin, Ran; Angelin, Alessia; Da Settimo, Federico; Martini, Claudia; Taliani, Sabrina; Zhu, Shigong; Wallace, Douglas C.
Summary The outer mitochondrial membrane (OMM) protein, the translocator protein 18 kDa (TSPO), formerly named the peripheral benzodiazepine receptor (PBR), has been proposed to participate in the pathogenesis of neurodegenerative diseases. To clarify the TSPO function, we identified the Drosophila homolog, CG2789/dTSPO, and studied the effects of its inactivation by P‐element insertion, RNAi knockdown, and inhibition by ligands (PK11195, Ro5‐4864). Inhibition of dTSPO inhibited wing disk apoptosis in response to γ‐irradiation or H2O2 exposure, as well as extended male fly lifespan and inhibited Aβ42‐induced neurodegeneration in association with decreased caspase activation. Therefore, dTSPO is an essential mediator of apoptosis in Drosophila and plays a central role in controlling longevity and neurodegenerative disease, making it a promising drug target.